Analysis of Government Regulation Number 28 of 2025 concerning the Implementation of Risk-Based Business Licensing: Impact on the Investment Climate and Foreign Investment in Indonesia - I Ketut Parikesit; Putu Eka Trisna Dewi (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Government Regulation of the Republic of Indonesia Number 28 Year 2025 concerning the Implementation of Risk-Based Business Licensing (RBBL) marks a fundamental policy reform in Indonesia's business licensing landscape. This regulation, which officially revokes and replaces Government Regulation Number 5 Year 2021, aims to simplify and accelerate the licensing process, focusing on increasing efficiency, transparency, and legal certainty for business actors. Significant changes include the application of binding Service Level Agreements (SLAs), a fictive-positive policy to prevent delays, simplification of procedures for Micro and Small Enterprises (MSEs), and strengthening the Online Single Submission (OSS) system as a single reference. The anticipated impact of the enactment of GR 28/2025 on Indonesia's investment climate is highly positive. This regulation is expected to increase the confidence of both domestic and foreign investors through greater certainty of time and more transparent processes, reduced bureaucracy, and minimized potential for corrupt practices. For Foreign Direct Investment (FDI), the ease of licensing and integrated access to various facilities and tax incentives through the OSS system will be a significant attraction. Nevertheless, the successful implementation of GR 28/2025 will largely depend on the government's ability to overcome operational challenges, including seamless system integration, human resource capacity building, and comprehensive socialization to all stakeholders.